Адаптація суднобудівного підприємства до змін стимулів його розвитку - Єфімова, Г. В.; Рогов, В. Г.; Iefimova, G. V.; Rogov, V. (Видавництво Львівської політехніки, 2019)
Визначено етапи адаптації суднобудівного підприємства до змін стимулів його розвитку. Розглянуто економіко-математичні моделі, що застосовують центральні банки для макроекономічного прогнозування, та запропоновано використовувати їх підприємствами суднобудування з метою прогнозування інфляції та курсу валют. Визначено інформаційне забезпечення та види кредитних та податкових стимулів розвитку підприємств суднобудування, сформульовано екзогенні й ендогенні індикатори раннього попередження змін стимулів та їхні граничні значення. Запропоновано види реагування на зміни кредитних та податкових стимулів.

The formation of the adaptation mechanism to the development incentives changes is especially relevant for shipbuilding enterprises. It is necessary to predict potential changes in legislation, lending, insurance, investment, to use the chances and to minimize the risks appropriately. In order to prevent the threats and use the additional opportunities, the shipbuilding company should analyze weak and strong signals coming from the external and internal environment, assess their impact on the effectiveness of its activities, in particular, by the business value indicator, and respond to them beforehand. The purpose of the study is to present the author’s vision regarding the formation of the early warning and response system to economic incentives for shipbuilding enterprises development. The stages of shipbuilding enterprise adaptation to its development incentives changes are determined. The economic-mathematical models used by central banks for macroeconomic forecasting are considered and suggested for shipbuilding enterprises in order to forecast inflation and exchange rates. The information support and the types of credit and tax incentives for shipbuilding enterprises development are defined. Exogenous and endogenous early warning indicators of incentives changes and their marginal values are formulated. The types of responses to credit and tax incentives changes are proposed. Shipbuilding companies need to identify strong and weak signals in the current perspective (during the year) and in the strategic perspective (from three to five years). It is advisable to organize two variants of the early warning and response system for shipbuilding enterprises: under normal conditions and when all external influences are negative. The forecast data obtained should be taken into account during elaboration, priority justification and feasibility analysis of alternative corporate development strategies. The purpose of the credit subsystem is to use credit incentives to provide financial support for business development strategies implementation and minimizing the negative impact of the high debt cost and the credit resources market unbalance risk on the enterprise financial performance. The tax early warning subsystem involves the information accumulation about the company’s potential threats and opportunities due to the taxation changes. In order to predict inflation and national currency exchange rate, shipbuilding enterprises need both to use ready made forecasts and to conduct their own research by expert judgement and by the combined application of economic and mathematical models: random walk model (RW), linear trend autoregression (LTAR), unobserved component (UC), vector standard and Bayesian auto regression (VAR and BVAR), linear regression (OLS), P*-model, ARIMA model etc. The early warning indicators systematization in terms of time and directions of factors influence allows timely and comprehensive assessment of the incentives impact on the decisions processing in the field of the enterprise financial activity. As a consequence of forecasting, the enterprise is able to determine specific measures for responding to weak and strong signals.
H.Shipbuilding enterprise adaptation to the changes in its development incentives
Keywords: адаптація; стимули; розвиток підприємства; система раннього попередження; кредитна підсистема; податкова підсистема; сильні сигнали; слабкі сигнали; adaptation; incentives; corporate development; early warning system; credit subsystem; tax subsystem; strong signals; weak signals; 005.1; 629.5